2017
DOI: 10.1111/acfi.12256
|View full text |Cite
|
Sign up to set email alerts
|

Implications of student‐generated screencasts on final examination performance

Abstract: Education Interest Group Symposium at the AFAANZ conference, for their valuable comments and suggestions concerning our research. In addition we would also like to thank Roger San for his assistance with this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(66 reference statements)
0
7
0
3
Order By: Relevance
“…While implementation of an assignment as this may have existed in the past, the ability to create this type of assignment is readily available to students via freely available software, institutionally subscribed resources, or their personal smartphone or tablet. Screencast assignments are documented in the literature of other disciplines like accounting [ 22 24 ] and education [ 25 , 26 ]. Faculty use of screencasts to deliver feedback on assignments is also demonstrated in the literature and was perceived by students taking part in the published studies to be more effective and favorable to written feedback [ 27 – 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…While implementation of an assignment as this may have existed in the past, the ability to create this type of assignment is readily available to students via freely available software, institutionally subscribed resources, or their personal smartphone or tablet. Screencast assignments are documented in the literature of other disciplines like accounting [ 22 24 ] and education [ 25 , 26 ]. Faculty use of screencasts to deliver feedback on assignments is also demonstrated in the literature and was perceived by students taking part in the published studies to be more effective and favorable to written feedback [ 27 – 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, researchers indicate that digital videos can be used as motivational tools (Holtzblatt & Tschakert, 2011;Bravo-Ibarra et al, 2010) and for increasing student satisfaction (Rezaie & Barani, 2011;Rodrigues, 2016), as well as providing an improvement in academic performance (Sargent et al, 2011;Wakefield et al, 2017;D'Aquila et al, 2019).…”
Section: Advantages and Disadvantages Of Using Digital Videomentioning
confidence: 99%
“…The employment of this technology has been positively evaluated in face-to-face teaching, especially in the pedagogical, motivational and student satisfaction spheres (Rezaie & Barani, 2011;Holtzblatt & Tschakert, 2011;Sargent, Borthick & Lederberg, 2011). Furthermore, studies such as those by Wakefield, Tyler, Dyson, andFrawley (2017) andD'Aquila et al (2019) have identified improvements in the performance of accounting students who have made use of digital videos as an aid to their studies.…”
Section: Introductionmentioning
confidence: 99%
“…Penugasan screencast dalam pendidikan akutansi dapat meningkatkan kinerja ujian akhir semester pada penelitian yang telah dilakukan (Wakefield, Tyler, Dyson, & Frawley, 2017). Dengan demikian screencast bisa dijadikan alat untuk meningkatkan kinerja pembelajaran pada saat pebelajar memproduksi screencast.…”
Section: Metodeunclassified